Effect of Different Storage Temperatures on Postharvest Quality and Antioxidant Capacity of Yellow-fleshed Peach - Chushan YUAN; Yunian HUANG; Xinrui DONG; Wei LIU; Donglin SU; Xiangrong ZHU (Shipin gongye ke-ji, 2023)
The effect of low temperature storage on the postharvest quality and antioxidant capacity of yellow-fleshed peach (YFP) was investigated. The YFP fruits were pre-cooled for 12 h after harvesting, and grouped and stored at 0, 4 and 10 ℃ in refrigeration. The quality parameters and antioxidant enzyme activities were determined. The results showed that the decay rate and browning index of YFP stored at 0 ℃ were 0, which were significantly lower than those of fruit stored at 4 and 10 ℃ (P<0.05). And membrane permeability of YFP stored at 0 ℃ was significantly suppressed. Compared with 4 and 10 ℃, the quality, total antioxidant capacity and antioxidant enzyme activity stored at 0 ℃ were all maintained at a higher level at the end of storage. The fruit hardness, contents of total sugar, soluble solid content (SSC), titratable acid (TA), vitamin C (VC), total phenol and total flavonoids were better maintained at 0 ℃. At the same time, the activities of polyphenol oxidase and peroxidase were inhibited and the fruit chilling injury was reduced at 0 ℃. At 4 and 10 ℃, hardness and VC content decreased significantly (P<0.05), while malondialdehyde (MDA) content increased rapidly (P<0.05). At present, the 19 physiological and biochemical parameters were separated into two distinct independent clusters were observed by hierarchical clustering analysis (HCA), which were generally consistent with the results of principal component analysis (PCA), the periods of 14~21 d were the quality deterioration points stored at different temperatures, and the first principal component (PC1) could well separate the hardness, VC content, TA and other indicators. The result could indicate the similarity and difference between physiological and biochemical indexes of YFP. Thus, the storage temperature on 0 ℃ can promote the quality and antioxidant ability of yellow-fleshed peach.